Bibliothek der Kirchenväter;: eine Auswahl patristischer Werke in deutscher Übersetzung. [Neue Aufl.] - Bardenhewer, Otto; Zellinger, Johannes; Martin, Joseph (Kösel-Pustet [etc.], 1911)
v. 1, Augustinus I / ed. Johann Nepomuk Espenberger. -- v. 2, Dionysius Areopagita / tr. Josef Stiglmayr. -- v. 3, Irenäus I / tr. E. Klebba. -- v. 4, Irenäus II / tr. E. Klebba. -- v. 5, Griechische Liturgien / tr. Remigius Storf. -- v. 6, Syrische Dichter [Cyrillonas, Baläus, Isaak von Antiochen, Jakob von Sarug] / tr. P.S. Landersdorfer. -- v. 7, Tertullian I / tr. K.A. Heinr. Kellner. -- v. 8, Augustinus IV / tr. Thomas Specht. -- v. 9, Eusebius Pamphili [of Caesarea] I / ed. Andreas Bigelmair. -- v. 10, Makarius des Ägypter / tr. Dionys Stiefenhofer. -- v. 11, Augustinus II / tr. Thomas Specht. -- v. 12, Frühchristliche Apologeten [Aristides von Athen, Justins der Martyrer, Tatian der Assyrer, Athenagoras von Athen]. -- v. 13, Athanasius I. -- v. 14, Frühchristliche Apologeten [Theophilus von Antiochen, Hermias der Philosoph, Minucius Felix, Firmicus Maternus, echte alte Märtyrerakten]. -- v. 15, Hieronymus I / tr. Ludwig Schade. -- v. 16, Augustinus II / tr. Alfred Schröder. -- v. 17, Ambrosius I / tr. Joh. Ev. Niederhuber. -- v. 18, Augustinus VII / tr. Alfred Hoffmann. -- v. 19, Augustinus VI / tr. Thomas Specht. -- v. 20, Sulpicius Severus, Vinzenz von Lerin, Benediktus. -- v. 21, Ambrosius II / tr. Joh. Ev. Niederhuber. -- v. 22, Persische Märtyrer / tr. Oskar Braun. -- v. 23, Johannes Chrysostomus I / tr. P. Joh. Chrysostomus Baur. -- v. 24, Tertullian II / tr. K.A. Heinrich Kellner. -- v. 25, Johannes Chrysostomus II / tr. P. Joh. Chrysostomus Baur. -- v. 26, Johannes Chrysostomus III / tr. P. Joh. Chrysostomus Baur. -- v. 27, Johannes Chrysostomus IV / tr. P. Joh. Chrysostomus Baur and August Naegle. -- v. 28, Augustinus III / tr. Alfred Schröder. -- v. 29, Augustinus IX / tr. Alfred Hoffmann. -- v. 30, Augustinus X / tr. Alfred Hoffmann. -- v. 31, Athanasius II. -- v. 32, Ambrosius III / tr. Joh. Ev. Niederhuber. -- v. 33, Justinus / tr. Philipp Haeuser. -- v. 34, Cyprian I / tr. Julius Baer. -- v. 35, Apostolischen Väter / tr. Franz Zeller. -- v. 36, Lactantius. -- v. 37, Ephräm der Syrer I / ed. Otto Bardenhewer. -- v. 38, Epiphanius von Salamis / tr. Josef Hörmann. -- v. 39, Johannes Chrysostomus V / tr. Josef Jatsch. -- v. 40, Hippolytus von Rom / tr. Graf Konrad Preysing. -- v. 41, Cyrillus von Jerusalem / tr. Philipp Haeuser. -- v. 42, Johannes Chrysostomus VI / tr. Josef Jatsch. -- v. 43, Petrus Chrysologus / tr. G. Böhmer. -- v. 44, Johannes von Damaskus / tr. Dionys Stiefenhofer. -- v. 45, Johannes Chrysostomus VII / tr. Wenzel Stoderl. -- v. 46, Basilius I / tr. Anton Stegmann. -- v. 47, Basilius II / tr. Anton Stegmann. -- v. 48, Origenes I / tr. Paul Koetschau. -- v. 49, Augustinus VIII / tr. P. Sigisbert Mitterer. -- v. 50, Theodoret I / tr. Konstantin Gutberlet. -- v. 51, Theodoret II / tr. Andreas Seider. -- v. 52, Origenes II / tr. Paul Koetschau. -- v. 53, Origenes III / tr. Paul Koetschau. -- v. 54, Leo der Grosse I / tr. Theodor Steeger. -- v. 55, Leo der Grosse II / tr. Theodor Steeger. -- v. 56, Gregor von Nyssa. -- v. 57, Armenische Kirchenväter I [Eznik, Koriun, Hatschachapatum] / ed. Simon Weber. -- v. 58, Armenische Kirchenväter II [Mambre, Verzanogh, Johannes Mandakuni, Elische] / ed. Simon Weber. -- v. 59, Gregor von Nazianz I / tr. Philipp Haeuser. -- v. 60, Cyprian II / tr. Julius Baer. -- v. 61, Ephräm der Syrer II / tr. Adolf Rücker. -- [unnumbered vol. following v. 61] index 1911-28, v. 1-61, 2 v. in 1. -- n.s. v. 1, Eusebius Pamphili [of Caesarea] II / tr. Phil. Haeuser. -- n.s. v. 2, Dionysius Areopagita II / tr. Joseph Stiglmayr. -- n.s. v. 3, Gregor der Grosse II / tr. Joseph Funk. -- n.s. v. 4, Gregor der Grosse I / tr. Joseph Funk. -- n.s. v. 5, Hilarius I / tr. Anton Antweiler. -- n.s. v. 6, Hilarius II / tr. Anton Antweiler. -- n.s. v. 7, Clemens von Alexandrien I. -- n.s. v. 8, Clemens von Alexandrien II. -- n.s. v. 9, Fulgentius von Ruspe / tr. Leo Kozelka. -- n.s. v. 10, Zeno von Verona / tr. Andreas Bigelmair. -- n.s. v. 11, Salvian von Marseille / tr. Anton Mayer. -- n.s. v. 12, Cyrillus von Alexandrien / tr. Otto Bardenhewer. -- n.s. v. 13, Augustinus XI / tr. Michael Schmaus. -- n.s. v. 14, Augustinus XII / tr. Michael Schmaus. -- n.s. v. 15, Johannes Chrysostomus VIII / tr. Wenzel Stoderl. -- n.s. v. 16, Hieronymus II / tr. Ludwig Schade. -- n.s. v. 17, Clemens von Alexandrien III. -- n.s. v. 18, Hieronymus III / tr. Ludwig Schade. -- n.s. v. 19, Clemens von Alexandrien IV. -- n.s. v. 20, Clemens von Alexandrien V.